Culture’s Place in the Foreign Language Classroom - Parent, Amanda (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2023)
This paper will first outline what culture is and what exactly is meant by intercultural communication in the foreign language (FL) classroom by analyzing theoretical texts on the topic. Then, this paper will discuss many studies on learning tasks that integrate culture from both foreign language classrooms in English-speaking countries as well as English as a foreign language (EFL) classrooms in other countries. This paper will describe each task and then demonstrate how they bolster students’ proficiency in writing or listening and speaking. Additionally, this paper will show that these tasks create a marked increase in students’ motivation and excitement to learn a new language.